Generation of a highly efficient and tissue-specific tryptophan hydroxylase 1 knockout mouse model. Issue 1 (December 2018) - Kim, Hyeongseok; Kim, Yeong; Choi, Wonsuk; Moon, Joon; Hwang, Inseon; Kim, Kyuho; Yadav, Vijay; Karsenty, Gerard; Jeong, Ji-Seon; Kim, Hail
Abstract Recent studies on tissue-autonomous serotonin (5-hydroxytryptamine [5-HT]) function have identified new roles for 5-HT in peripheral organs. Most of these studies were performed by crossing mice carrying theTph1 tm1Kry allele with tissue specific Cre mice. In the present study, we found that 5-HT production was not completely abolished inTph1 tm1Kry KO mice. The residual 5-HT production inTph1 tm1Kry KO mice is attributed to the expression of a truncated form of TPH1 containing the catalytic domain. Hence, in an effort to obtain mice with aTph1 null phenotype, we generated mice harboring a newTph1 floxed allele, Tph1 tm1c, targeting exons 5 and 6 which encode the catalytic domain of TPH1. By crossing the newTph1 floxed mice with villin-Cre or insulin-Cre mice, we observed near-complete ablation of 5-HT production in the intestine and β cells. In conclusion, this improvedTph1 floxed mouse model will serve as useful and accurate tool for analyzing peripheral 5-HT system.